Emerging therapies and recent advances for Tourette syndrome - Chih-Yi Chou; Julian Agin-Liebes; Sheng-Han Kuo (Heliyon, 2023)
Tourette syndrome is the most prevalent hyperkinetic movement disorder in children and can be highly disabling. While the pathomechanism of Tourette syndrome remains largely obscure, recent studies have greatly improved our knowledge about this disease, providing a new perspective in our understanding of this condition. Advances in electrophysiology and neuroimaging have elucidated that there is a reduction in frontal cortical volume and reduction of long rage connectivity to the frontal lobe from other parts of the brain. Several genes have also been identified to be associated with Tourette syndrome. Treatment of Tourette syndrome requires a multidisciplinary approach which includes behavioral and pharmacological therapy. In severe cases surgical therapy with deep brain stimulation may be warranted, though the optimal location for stimulation is still being investigated. Studies on alternative therapies including traditional Chinese medicine and neuromodulation, such as transcranial magnetic stimulation have shown promising results, but still are being used in an experimental basis. Several new therapies have also recently been tested in clinical trials. This review provides an overview of the latest findings with regards to genetics and neuroimaging for Tourette syndrome as well as an update on advanced therapeutics.